Spatial Study of Pengging Tourism Area as A Regional Flagship Tourism Development - Salamah, Yeni Noor; Sari, Dewi Novita; Fatmawati, Hanifah (Universitas Muhammadiyah Surakarta, 2024)
In the highly competitive tourism industry, management is prepared to tackle competition through continuous infrastructure development and the addition of supporting facilities. They have also readied skilled human resources. Marketing strategies such as billboard placement, brochure distribution, and banners have been implemented to attract more tourists to Pengging. Facilities are added to enhance visitor comfort, making this research well-suited for qualitative methods. Developing tourist destinations using a spatial approach should consider regional characteristics in policy formulation. Limited research exists on this topic in Indonesia, making this study potentially valuable for government tourism planning. It aims to assess Pengging's potential, attractiveness, and development plan, using SWOT analysis based on geographical, demographic, socio-cultural, economic, and infrastructure indicators. The conclusions suggest managing visitor centers, enhancing tourism products, environmental management, visitor capacity, marketing, human resources, institution development, and spatial planning for Pengging tourist attraction area. This study provides spatial analysis-based recommendations for the development of Pengging tourism as a regional flagship destination. The study is unique in its integration of spatial approaches and local potential analysis, which have rarely been applied before. The findings are valuable for supporting sustainable tourism management strategies, enhancing tourism appeal, boosting the local economy, and promoting environmental conservation.